1980
DOI: 10.1038/288286a0
|View full text |Cite
|
Sign up to set email alerts
|

The enkephalinase inhibitor thiorphan shows antinociceptive activity in mice

Abstract: There is both theoretical and therapeutic interest in establishing whether the signals conveyed by the enkephalins are turned off under the action of a specific peptidase which might, in this case, represent a target for a new class of psychoactive agents. Enkephalinase, a dipeptidyl carboxypeptidase cleaving the Gly3-Phe4 bond of enkephalins and distinct fropm angiotensin coverting enzyme (ACE), might be selectively involved in enkephalinergic transmission. It is a membrane-bound enzyme whose localization in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
254
1
2

Year Published

1984
1984
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 711 publications
(263 citation statements)
references
References 30 publications
6
254
1
2
Order By: Relevance
“…These observations suggested that 5-HT-induced tachycardia is selectively sensitive to capsaicin treatment and that the effect might be mediated through release of cardiotonic peptide(s). Furthermore, we found that 5-HT-induced tachycardia was potentiated by thiorphan, an inhibitor of peptide degeneration (16). This result further supported the suggestion that the effect of 5-HT might be mediated through release of bioactive peptide(s).…”
Section: Discussionsupporting
confidence: 77%
“…These observations suggested that 5-HT-induced tachycardia is selectively sensitive to capsaicin treatment and that the effect might be mediated through release of cardiotonic peptide(s). Furthermore, we found that 5-HT-induced tachycardia was potentiated by thiorphan, an inhibitor of peptide degeneration (16). This result further supported the suggestion that the effect of 5-HT might be mediated through release of bioactive peptide(s).…”
Section: Discussionsupporting
confidence: 77%
“…However, Cohen et al (2) showed that the inhibitory potency of enkephalin in guinea-pig ileum was not enhanced by puromycin, but augmented by bestatin, an aminopeptidase inhibitor of bacterial origin (7); and the degradation of 3H-enkephalin after incubation with guinea-pig ileum was not altered with puromycin, but decreased with bestatin. On the other hand, it was reported (3) that the inhibitory potency of enkephalin in guinea-pig ileum was not altered with either thiorphan, an inhibitor of "enkephalinase" (8) , or captopril, an angio tensin converting enzyme inhibitor (9). However, Kosterlitz and his colleague (4,5) showed that the greatest increase in potency of enkephalin in guinea-pig ileum was obtained with the combination of bestatin, captopril, thiorphan and L-leucyl-L-leucine.…”
mentioning
confidence: 99%
“…Puromycin (100 /IM) and bestatin (10 PM) inhibited almost completely the activity of the electric organ aminopeptidase (90 and 86% inhibition respectively) and had no activity (bestatin) or low inhibitory activity (puromycin) toward the soluble endopeptidase. Thiorphan (10 pM), a potent inhibitor of the brain endopeptidase enkephalinase [21], did not affect the aminopeptidase activity but completely inhibited the soluble endopeptidase (94% inhibition). Similar results were obtained with the membrane associated endopeptidase.…”
Section: Resultsmentioning
confidence: 98%